Entrepreneurial Orientation and Organizational Effectiveness: The Mediating Effect of Organizational Engagement Among Managerial Leaders - Dedy Budiman; Eko Suhartanto (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study investigates how three core dimensions of entrepreneurial orientation (EO) innovativeness, proactiveness, and risk-taking influence organizational effectiveness, and whether organizational engagement mediates these relationships. Data were collected from 138 managerial leaders across property, automotive, banking, financial services, and manufacturing industries using an online questionnaire. EO was measured using adapted Covin and Slevin items, organizational engagement using Saks' (2006) scale, and organizational effectiveness using a 14-item scale adapted from Gold et al. (2001), all rated on a seven-point Likert scale. Multiple regression and Baron and Kenny's (1986) mediation procedure were applied. Results reveal that innovativeness (β = 0.263, p < .001) and proactiveness (β = 0.447, p < .001) positively predict organizational effectiveness, while risk-taking yields no significant direct effect (β = 0.154, p = .084). Organizational engagement partially mediates the relationship between innovativeness and proactiveness, whereas the mediation of the relationship between innovativeness and risk-taking is inconclusive. Findings advance EO research by demonstrating dimension-specific effects and positioning engagement as a critical psychological conduit linking entrepreneurial behaviors to collective performance.